Renal and Neurologic Benefit of Levosimendan vs Dobutamine in Patients With Low Cardiac Output Syndrome After Cardiac Surgery: Clinical Trial FIM-BGC-2014-01 - Jose L. Guerrero-Orriach; Jose L. Guerrero-Orriach; Jose L. Guerrero-Orriach; Alfredo Malo-Manso; Alfredo Malo-Manso; Marta Ramirez-Aliaga; Marta Ramirez-Aliaga; Ana Isabel Florez Vela; Manuel Galán-Ortega; Manuel Galán-Ortega; Isabel Moreno-Cortes; Inmaculada Gonzalez-Almendros; et al. (Frontiers in Pharmacology, 2020)
BackgroundLow-cardiac output syndrome (LCOS) after cardiac surgery secondary to systemic hypoperfusion is associated with a higher incidence of renal and neurological damage. A range of effective therapies are available for LCOS. The beneficial systemic effects of levosimendan persist even after cardiac output is restored, which suggests an independent cardioprotective effect.MethodsA double-blind clinical trial was conducted in patients with a confirmed diagnosis of LCOS randomized into two treatment groups (levosimendan vs. dobutamine). Monitoring of hemodynamic (cardiac index, systolic volume index, heart rate, mean arterial pressure, central venous pressure, central venous saturation); biochemical (e.g. creatinine, S100B protein, NT-proBNP, troponin I); and renal parameters was performed using acute kidney injury scale (AKI scale) and renal and brain ultrasound measurements [vascular resistance index (VRI)] at diagnosis and during the first 48 h.ResultsSignificant differences were observed between groups in terms of cardiac index, systolic volume index, NT-proBNP, and kidney injury stage at diagnosis. In the levosimendan group, there were significant variations in AKI stage after 24 and 48 h. No significant differences were observed in the other parameters studied.ConclusionLevosimendan showed a beneficial effect on renal function in LCOS patients after cardiac surgery that was independent from cardiac output and vascular tone. This effect is probably achieved by pharmacological postconditioning.Clinical Trial RegistrationEUDRA CT, identifier 2014-001461-27. https://www.clinicaltrialsregister.eu/ctr-search/search?query=2014-001461-27